2014
DOI: 10.1016/j.aap.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Health status recovery at one year in children injured in a road accident: A cohort study

Abstract: Despite the frequency of traumatic injuries due to road accidents and potential importance of identifying children at risk of impaired recovery one year after a road accident, there is a lack of data on long-term recovery of health status, except in children with severe traumatic brain injury. The aim of the present study was to evaluate predictive factors of recovery in children one year after road traffic injuries. The prospective cohort study was composed of children aged <16 years, admitted to public or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…As summarized in Table 4 , only one study (of nine studies assessing variations by sex) found a difference with girls more likely to be lost to follow-up [ 52 ]. The one study examining parental occupation found higher losses to follow-up among children of parents with low occupation level [ 6 ]. The study assessing socio-economic status found loss to follow-up was highest among those in the lowest income quintile [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As summarized in Table 4 , only one study (of nine studies assessing variations by sex) found a difference with girls more likely to be lost to follow-up [ 52 ]. The one study examining parental occupation found higher losses to follow-up among children of parents with low occupation level [ 6 ]. The study assessing socio-economic status found loss to follow-up was highest among those in the lowest income quintile [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…More nuanced analyses can also uncover possible interactions between different factors. For example, a Californian study which found no racial/ethnic disparity in mortality for injured children suggested that the unexpected finding was possibly due to insurance coverage being less of a barrier for children in California than for adults and children elsewhere in the United Sates, and because California’s racial diversity led to culturally competent care which delivered better outcomes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 McCarthy et al 22 followed up injured children longitudinally and found 40% of those with head injuries to have substantial impairments at 12 months. Another study by Batailler et al 27 among children injured in traffic crashes found that 32.3% of them had not fully recovered at 12 months. Health deficits among children with injuries were also documented in a study by Holbrook et al 28 in which children were followed for 24 months.…”
Section: Discussionmentioning
confidence: 96%
“…Изучение этих измене-ний для анализа эффективности лечения и реа-билитации становится все более актуальной за-дачей, а представление результатов исследования с использованием международных показателей эффективности способствует обобщению между-народного клинического опыта. При этом особое значение приобретает внедрение «количествен-ной методики оценки исходов, с известной и до-казанной точностью позволяющей проводить все необходимые статистические операции» в соот-ветствии с принципами доказательной медицины [10,55,56].…”
Section: обзоры литературыunclassified